(3cJGH aj Yed Tcd eLSe Pi CQHYI YTQI bGYOI JMjW Hg cQI eYdheIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3fQjO Cf fHjf cja fYed TcdkG eLSeG PG CQHY YTQI bGYOg eJSGhi GdCVdGY hGdRhGjG JMjW Hg cQI eYdheI s
(3BNQgG (B:s
(3hVY gPG GdTcd Pi GdCQHY YTQI bGYOI GdPi PcQfG eKd fUa bWQ GdcQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B108 - (3U(B115s
(3ajgG QSe GdTcd GdeLSes
(3efShN ef OSJhQ KGHJ Hf bQI GdPi HNWgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B72 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs